Application of Liquid Silica Nutrients to Plant Growth Analysis and Rice Productivity Affected by Salt Stress (NaCl) - Nasrudin Nasrudin; Aditya Wahyudhi (Hasanuddin University, 2021)
The use of liquid silica nutrients under salt stress can increase plant resistance through cell wall thickening which will also affect to increase productivity. The study aims to examine the effect of liquid silica nutrients to plant growth analyze and rice productivity affected by salt stress (NaCl). The experiment used a factorial completely randomized design. The first factor was NaCl concentrations consisted of 0 dS m-1, 4 dS m-1, 8 dS m-1, and 12 dS m-1. The second factor was application of liquid silica nutrients consisted of 0.2 mL L-1, 0.4 mL L-1, and 0.6 mL L-1. The treatments were repeated three times. Increasing the NaCl concentration to 12 dS m-1 when the plants were 4 weeks after planting caused a decrease in leaf area index. The addition of liquid silica nutrients with concentration up to 0.6 mL L-1 under salted conditions led to an increase in root shoot ratio, and the addition of liquid silica nutrients with concentration of 0.6 mL L-1 in salted conditions of 4 dS m-1 caused an increase in plant growth rate. The results showed that the leaf area index, leaf area ratio, root shoot ratio, and plant growth rate were positively correlated with plant biomass. Furthermore, the root shoot ratio had a positively correlated with productivity, the harvested index had a positively correlated with the number of productive tillers, percentage of filled grains, and rice productivity. However, the net assimilation rate and harvested index were negatively correlated with plant biomass.